Alternative Al production methods. (1st June 2013) - Dewan, M A; Rhamdhani, M A; Brooks, G A; Monaghan, B J; Prentice, L
<x xml:space="preserve">Abstract</x> It has been widely claimed that direct and indirect carbothermic reduction of alumina for the production of aluminium have the potential to consume less energy, generate fewer perfluorocarbons and have lower total greenhouse gas emissions compared to the Hall-Héroult process. A review of alternative aluminium production techniques focusing on the indirect carbothermal reduction routes has been presented in the Part 1 paper. In this Part 2 paper, systematic thermodynamic analyses of indirect carbothermal reduction routes are presented. These include the analyses of the Stage 1 of the process where alumina is converted to intermediate aluminium compounds before they are further reduced to aluminium metal in the subsequent stages. The results suggested that in the Stage 1, high alumina conversion at the process conditions studied can be achieved through three process routes: halide (chloride), nitride and sulphide routes. Thermodynamic analyses were also carried out for the Stage 2 where the intermediate aluminium nitride, chlorides or sulphides are reduced to aluminium through thermal dissociation, thermal disproportionation and/or electrolysis. Analysis of the results suggests aluminium may be extracted from AlN using thermal dissociation, while disproportionation and electrolysis are more suitable for AlCl3 and Al2S3.